Accumulation of metal (Cd, Cr, Cu, Ni and Pb) contaminated water using Bacopa monnieri, Lilaeopsis brasiliensis, Hemianthus callitrichoides and Glossostigma elatinoides - Othman, Rashidi; Abu Yazid, Anis Fatihah (2016)
The pollution of aquatic ecosystems in Malaysia has emerged as a major ecological problem coinciding with rapid industrialization and urbanization. The contamination often contributed by industries bearing heavy metals, such as Cd, Cr, Cu, Ni, and Pb can cause significant ecological and environmental problems. Due to their high solubility in water environment, they can easily enter food chain, thus making it a serious health hazards for human and other organisms. Presently, the study on phytoremediation by using macrophytes are still on-going and appears to be one of prospective alternative and innovative technology that can be applied at contaminated aquatic environments. However, it is noted that careful evaluation of its applicability and effectiveness will be required. Cd, Cr, Cu, Ni, and Pb remediation in water was assessed through selected aquatic plant species, which are Bacopa monnieri, Lilaeopsis brasiliensis, Hemianthus callitrichoides and Glossostigma elatinoides via in-vitro model system. Based on the bioconcentration factor (BCF), the capability of the plant species to remediate Cd, Cr, Cu, Ni, and Pb can be assessed and it was concluded that all of the plants have different capabilities of heavy metals uptake and shown vary signs of stress and symptoms of toxic poisoning.